Woodstock Rocks: From Acheulean to Iron Age in the Waterberg, Limpopo Province, South Africa - Lyn Wadley; Wim Biemond; Ghilraen Laue; Christine Sievers; Carolyn Thorp; Michiel de Kock (Southern African Field Archaeology)
The cliff terrace site, Woodstock Rocks, was exploited occasionally by hominins from the Earlier Stone Age to the Iron Age. A small excavation uncovered an Acheulean quartzite workshop with many flakes, but lacking large cutting tools and without organic preservation. Below the workshop site, a ferricrete river terrace cements Acheulean lithics that include large cutting tools, giant flakes and heavy-duty scrapers. A palaeomagnetic study reveals reversed polarity, implying that the ferricrete formation likely took place during the Matuyama Chron and that the lithic assemblage is older than 780 000 years. The cliff face was painted expansively, but both the Bushman and Iron Age farmer art is faded. There are some rare images including a wild dog, a bird and a possible genet. The southern edge of the cliff terrace has Middle and Later Stone Age lithics on the surface and talus slope, as well as grindstones, and ceramics that include Bambata sherds from six vessels. The proximity to the Mokolo River and sources of rocks for knapping, as well as smooth rock walls for painting ensured repeated Woodstock Rocks visits (not necessarily occupation) for generations of Homo sapiens visitors, as well as earlier hominins.